Gender Related Change in Morphometry of Normal Lumbar Intervertebral Disc by MRI in a Tertiary Level Hospital of Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Morphometry of lumbar intervertebral disc is valuable for the diagnostics and therapeutic purposes and also for adequate planning, preparation and preoperative selection of prosthetic implants. This study was aimed to measure the morphometry of all lumbar intervertebral discs in relation to sex. Materials and methods: This cross-sectional analytical study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram, upon 50 male and 50 female from April 2021 to March 2022. All participants with normal lumber MRI scan as certified by expert radiologist were recruited from Radiology and Imaging department of Chittagong Medical College Hospital (CMCH) as per inclusion criteria. T2 weighted sagittal lumbar normal MRI scans were included in this study. All measurements such as Superior Length of the disc (SL) and Inferior Length of the disc (IL) Anterior Disc Height (ADH) midpoint disc height (MDH) and Posterior Disc Height (PDH) were taken and recorded in a predesigned case-record form. Measurements were presented as mean±SD and were compared by unpaired student’s t test. Data were analyzed by SPSS (Version 26.0). Finally the results were presenters using tables and figures. Results: In this study mean SL and IL of male were greater than female and showed an increase from L1-L2 to L4L5 but unpaired student’s t-test revealed that the difference in SL and IL were not statistically significant in any sex (p>0.05). For ADH, MDH and PDH all mean values were found to be higher in males than in females except for the MDH in the L1-L2 level and for ADH in the level of L5-S1.Also the mean of ADH, MDH and PDH were not statistically significant in relation to sex (p>0.05). Conclusion: The result of the present study provides some baseline information about morphology of lumbar intervertebral disc of normal Bangladeshi population and encourages further research in this field.Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 10-14